Implant abutment deformation during prosthetic cylinder screw tightening: An in vitro study - Neto, Rafael Tobias Moretti; Moura, Márcio Silva; Souza, Edson Antônio Capello; Rubo, José Henrique (My University, 2009)
Purpose: Nonpassive fit frameworks are believed to lead to implant overload and consequently loss of osseointegration. This is one of the most commonly reported failures of implant prostheses. In an ideal situation of passive fit, when torque is applied to bring the abutment-cylinder interface together some amount of deformation can be expected, and it should be homogeneous along the periphery of the abutment. The aim of this study was to verify the amount of abutment deformation that can be expected when a free-standing cylinder is screwed into place. This could give insight into what should be accepted as passive fit. Materials and Methods: Strain gauges were bonded to the sides of five standard abutments that had machined palladiumsilver cylinders or cobalt-chromium cast cylinders screwed into place. Measurements were taken to verify the deformation at each site. Results: Values of abutment deformation after abutment screw tightening ranged from -127.70 to -590.27 µε. The deformation recorded for palladium-silver prosthetic cylinder tightening ranged from 56.905 to -381.50 µε (mean: 173.298 µε) and from -5.62638 to -383.86 µε (mean: 200.474 µε) for cobalt-chromium cylinders. There was no statistically significant difference among the two groups. Conclusion: Both abutment screw tightening and prosthetic cylinder screw tightening result in abutment deformation, which is compressive most of the time. © 2009 by Quintessence Publishing Co Inc.